Association between Maternal Symptoms of Sleep Disordered Breathing and Fetal Telomere Length - Salihu, Hamisu M. (Sleep, 2015)
STUDY OBJECTIVES: Our investigation aims to assess the impact of symptoms of maternal sleep-disordered breathing, specifically sleep apnea risk and daytime sleepiness, on fetal leukocyte telomere length. PARTICIPANTS AND SETTING: Pregnant women were recruited upon hospital delivery admission. INTERVENTIONS: Sleep exposure outcomes were measured using the Berlin Questionnaire to quantify sleep apnea and the Epworth Sleepiness Scale to measure daytime sleepiness. Participants were classified as “High Risk” or “Low Risk” for sleep apnea based on responses to the Berlin, while “Normal” or “Abnormal” daytime sleepiness was determined based on responses to the Epworth. DESIGN: Neonatal umbilical cord blood samples (N = 67) were collected and genomic DNA was isolated from cord blood leukocytes using Quantitative PCR. A ratio of relative telomere length was derived by telomere repeat copy number and single copy gene copy number (T/S ratio) and used to compare telomere lengths. Bootstrap and ANOVA statistical procedures were employed. MEASUREMENTS AND RESULTS: On the Berlin, 68.7% of participants were classified as Low Risk while 31.3% were classified as High Risk for sleep apnea. According to the Epworth scale, 80.6% were determined to have Normal daytime sleepiness, and 19.4% were found to have Abnormal daytime sleepiness. The T/S ratio among pregnant women at High Risk for sleep apnea was significantly shorter than for those at Low Risk (P value < 0.05), and the T/S ratio among habitual snorers was significantly shorter than among non-habitual snorers (P value < 0.05). Although those with Normal Sleepiness had a longer T/S ratio than those with Abnormal Sleepiness, the difference was not statistically significant. CONCLUSION: Our results provide the first evidence demonstrating shortened telomere length among fetuses exposed to maternal symptoms of sleep disordered breathing during pregnancy, and suggest sleep disordered breathing as a possible mechanism of accelerated chromosomal aging. CITATION: Salihu HM, King L, Patel P, Paothong A, Pradhan A, Louis J, Naik E, Marty PJ, Whiteman V. Association between maternal symptoms of sleep disordered breathing and fetal telomere length. SLEEP 2015;38(4):559–566.